Exploring Collaboration and Partnerships: A Qualitative Study on Strategic Alliances and Business Networking for Value Creation - Mariam, Siti (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study investigates the dynamics, challenges, and opportunities in strategic alliances, business networking, and value-creation strategies in contemporary business environments. The research explores collaborative endeavors' motivations, mechanisms, and outcomes, drawing on insights from qualitative literature reviews and theoretical frameworks. The methodology involves a comprehensive selection of scholarly sources, systematic data collection methods, and rigorous data analysis techniques. Through thematic analysis and interpretation of existing literature, the study identifies key themes such as motivations for strategic alliances, mechanisms for value creation, and challenges in collaborative relationships. The findings reveal that strategic alliances are driven by traditional factors such as resource access and risk sharing and emerging trends like digitalization, globalization, and sustainability. Business networking is crucial in information exchange, resource access, and opportunity identification facilitated by digital platforms and online communities. Value creation in collaborative endeavors requires effective coordination, alignment of interests, and trust-building mechanisms among participating parties. The study contributes to understanding collaboration and networking dynamics, offering insights for practitioners and policymakers to foster successful partnerships and drive innovation and sustainable growth.